Metabolic Profiles of Carbohydrates in Streptococcus thermophilus During pH-Controlled Batch Fermentation - Liu, Gefei; Qiao, Yali; Zhang, Yanjiao; Leng, Cong; Chen, Hongyu; Sun, Jiahui; Fan, Xuejing; Li, Aili; Feng, Zhen (Frontiers in Microbiology, 2020)
Revealing the metabolic profiles of carbohydrates with their regulatory genes and metabolites is conducive to understanding their mechanism of utilization in Streptococcus thermophilus MN-ZLW-002 during pH-controlled batch fermentation. Transcriptomics and metabolomics were used to study carbohydrate metabolism. More than 200 unigenes were involved in carbohydrate transport. Of these unigenes, 55 were involved in the phosphate transport system, which had higher expression levels than those involved in ABC protein-dependent systems, permeases and symporters. The expression levels of the genes involved in the carbohydrate transport systems and phosphate transport system were high at the end-lag and end-exponential growth phases, respectively. In addition, 166 differentially expressed genes associated with carbohydrate metabolism were identified. Most genes had their highest expression levels at the end-lag phase. The pfk, ldh, zwf and E3.2.1.21 genes involved in the glycolytic pathway had higher expression levels at the end-exponential growth phase than the mid-exponential growth phase. The results showed high expression levels of lacZ and galKTM genes and reabsorption of extracellular galactose. S. thermophilus MN-ZLW-002 can metabolize and utilize galactose. Overall, this comprehensive network of carbohydrate metabolism is useful for further studies of the control of glycolytic pathway during the high-density culture of S. thermophilus.